Performance of serum and dried blood spot acylcarnitine profiles for detection of fatty acid β‐oxidation disorders in adult patients with rhabdomyolysis. Issue 2 (8th January 2013) - Al‐Thihli, Khalid; Sinclair, Graham; Sirrs, Sandra; Mezei, Michelle; Nelson, Judie; Vallance, Hilary
Abstract: Background: Plasma/serum and dried blood spot (DBS) acylcarnitine profiles (ACPs) are key to the diagnosis of mitochondrial fatty acid β‐oxidation disorders (FAODs). Despite their significant clinical applications, limited published data exists to compare their sensitivities and specificities. We retrospectively evaluated these two methods in adult patients with a history of rhabdomyolysis; investigated for an underlying FAOD. Methods: A retrospective study was completed for adult patients (investigated between 2003 and 2011) meeting the inclusion criteria of a history of recurrent rhabdomyolysis or one episode of rhabdomyolysis with a history of exercise intolerance. All subjects underwent investigations for an underlying FAOD including DBS and serum ACP analysis concurrently collected during a symptom‐free period, and skin biopsy for cultured fibroblast fatty acid oxidation studies or enzyme activity measurement, as indicated, with or without molecular confirmation. Their medical records were reviewed, and the performance of the two methods were compared. Results: Seven out of 31 subjects (22.6 %) were diagnosed with an underlying FAOD. Long chain acylcarnitines were more markedly elevated in serum samples from confirmed CPTII cases ( n = 4) as compared to matched DBS profiles. The sensitivity and specificity of DBS ACP was 71.4 % (95 % CI, 0.30–0.95) and 100 % (95 % CI, 0.79–1.00), respectively, compared to a sensitivity of 100 % (95 % CI, 0.56–1.00) and a specificity of 94.7 % (95 % CI, 0.72–1.00) for serum ACP. Conclusion: FAODs appear to be a common cause of recurrent rhabdomyolysis or rhabdomyolysis with a history of exercise induced myalgia. At least historically, FAODs maybe underdiagnosed in adults with rhabdomyolysis. This study suggests that serum ACP might be more sensitive than DBS ACP for detection of an underlying FAOD in adults with rhabdomyolysis while asymptomatic.